EFEKTIVITAS PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBLEM POSING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMP NEGERI 10 PADANGSIDIMPUAN - Siregar, Eva Yanti; Ardiana, Nunik; Nasution, Abdul Latif (JURNAL MathEdu (Mathematic Education Journal), 2025)
This research aims to describe the effectiveness of mathematics learning using a problem posing approach on students' critical mathematical thinking abilities in class VIII-2 of SMP Negeri 10 Padangsidimpuan. This research was conducted using an experimental method (one group pretest post test design) with a sample of 21 students and taken using a simple random sampling technique. Observations and tests are used in data collection. Based on the descriptive analysis, it was found that (a) the average use of the approach problem posing was 2.95 (good category) and (b) the average students' mathematical critical thinking ability before using the approach problem posing was 39.81 (failed) and after using the approach problem posing it was 39.41 (failed). 83.86 (good category). Furthermore, based on inferential statistics using the t test (SPSS 26) and N-Gain, the results showed a significant value of less than 0.05 (0.001<0.05) and g = 0.79 (high category). This means that the problem posing approach is very effectively used for students' critical mathematical thingking at SMP Negeri 10 Padangsidimpuan.